2019
DOI: 10.33085/jkg.v2i2.4316
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Risiko dengan Kejadian Hipertensi di Wilayah Kerja Puskesmas Takalala Kecamatan Marioriwawo Kabupaten Soppeng

Abstract: Hipertensi atau tekanan darah tinggi merupakan kondisi ketika seseorang mengalami kenaikan tekanan darah baik secara lambat atau mendadak. Menurut WHO penyakit tidak menulartelah menjadi penyebab kematian terbesardi dunia. disebutkan bahwa hampir 17 jutaorang meninggal lebih awal tiap tahunnyasebagai akibat epidemik penyakit tidak menular. Pada tahun 2025 nanti, angka ini kemungkinan akan meningkat menjadi 29,2%. Dari 972 juta penderita hipertensi, 639 juta berada di negara sedang berkembang, termasuk Indonesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 2 publications
1
5
0
13
Order By: Relevance
“…The genetic role in the incidence of hypertension is proven by the finding that hypertension is more common in monozygotic twins (one egg cell) than in heterozygous twins (different eggs). A patient who has the genetic nature of primary (essential) hypertension, if left naturally without any intervention therapy, together with his environment will cause his hypertension to develop and in about 30-50 years, signs and symptoms of hypertension will appear (Musfirah & Masriadi, 2019). In this study, the results obtained a P-Value of 0.305, which means that H0 is accepted, that is, there is no relationship between genetic history and the prevalence of hypertension.…”
Section: Discussionmentioning
confidence: 59%
“…The genetic role in the incidence of hypertension is proven by the finding that hypertension is more common in monozygotic twins (one egg cell) than in heterozygous twins (different eggs). A patient who has the genetic nature of primary (essential) hypertension, if left naturally without any intervention therapy, together with his environment will cause his hypertension to develop and in about 30-50 years, signs and symptoms of hypertension will appear (Musfirah & Masriadi, 2019). In this study, the results obtained a P-Value of 0.305, which means that H0 is accepted, that is, there is no relationship between genetic history and the prevalence of hypertension.…”
Section: Discussionmentioning
confidence: 59%
“…Residents with low education are associated with low awareness of healthy living behaviors and inadequate access to healthcare facilities, thereby increasing the risk of unhealthy lifestyles. 18,19 Based on previous studies, it was found that smoking behavior has a significant relationship with hypertension in adolescents and severe stress in adolescents. [20][21][22] Smoking by adolescents is a risk factor for dietary mistakes, poor oral health, and more dynamic damage to teeth, which may result in pain and tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…Menurut WHO Faktor yang tidak dapat diubah yakni memiliki riwayat penyakit hipertensi yang diturunkan dari keluarga, berusia 65 tahun dan penyakit penyerta (Rahcmawati, et al 2021). Sedangkan faktor tidak dapat diubah atau dikontrol adalah kelebihan berat badan, minimnya kegiatan yang melibatkan gerak fisik, mengkonsumsi rokok dan kopi, sensitivitas terhadap natrium, kadar kalium rendah, mengkonsumsi minuman beralkohol, pola makan yang kurang baik, dan Stres (Musfirah & Masriadi, 2019).…”
Section: Pendahuluanunclassified